Knowledge of Medical Records Staff of Mazandaran University of Medical Sciences Regarding the Maintenance of Patient Records after the Hospital Closure, 2009-2011 - Azar Kabirzadeh; Benyamin Mohseni Saravi; Ebrahim Bagherian Farahabadi; Hasan Siamian (Electronic Physician, 2011)
Objective: The objective of this study was to evaluate the Knowledge of Medical Records Staff of Mazandaran University of Medical Sciences Regarding the Maintenance of Patient Records after the Hospital ClosureMethods: This is a descriptive and cross-sectional study. There are 103 employees at the medical records department in the province of Mazandaran, 21 of whom did not agree to participate in the study. Therefore, 82 questionnaires were analyzed. Results: Of the 103 employees of the medical records department of hospitals run by the Mazandaran University of Medical Sciences, those not wishing to participate in the study were omitted. Thus, 82 questionnaires were analyzed. Results showed that two respondents (2.6%) had M.Sc. degrees, 37 (45.7%) had B.Sc. degrees and 42 (51.9%) were technicians of medical records. Eight respondents (10.1%) were trained in HIM responsibilities during a hospital closure, and 71 respondents (89.9%) had no training in this topic. Conclusion: Based on the answers provided, the results showed no significant relationship between general work experience and specific work experience in medical records. The correct answers are probably attributable to the fact that respondents received training related to other aspects of medical records and used that knowledge inferentially to give correct answers. Clearly, this training can reduce the chances of mistakes. Furthermore, results from this study indicate it is necessary to pass laws concerning the above-mentioned files, and that priority must be given to such legislation.